The Effect of Board of Director's Characteristics on The Corporate Social Responsibility Disclosure: Earnings Management As a Moderator In Iraq Companies - Hayder Zghair Idan; Nor Hanani Ahamad Rapani; Azam Abdelhakeem Khalid; Firas Salman Khudhair (Zien Journals, 2022)
The purpose of this paper is to examine board characteristics like independence, size, and meetings affect a developing country's corporate social responsibility disclosures (CSRD). In addition, this study examines also the effect of earnings management on the relationship between board of director characteristics and CSRD in Iraqi companies.
Keywords: Board of Director's Characteristics; Corporate Social Responsibility Disclosure; Earnings; Companies